1960
DOI: 10.1149/1.2427787
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Oxidation of Pure Tungsten from 500° to 1300°C

Abstract: Kinetic studies were made on the oxidation of tungsten from 500 ~ to 1300~ for time periods up to 6 hr, and for oxygen pressures from 0.1 atm to 0.00132 arm. The rate data were fitted to the parabolic rate law. A number of deviations and transitions were observed. For all of the experiments the initial slopes of the parabolic rate law plots were smaller than the final values found for thick films. A transition in the rate of oxidation was observed for weight gains of 2500-4000 ~g/cm ~ at temperatures of 650~17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
1

Year Published

1967
1967
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(41 citation statements)
references
References 11 publications
6
34
1
Order By: Relevance
“…This agrees with the numerous discrepancies reported in the literature concerning kinetics, composition and structure of the oxide scale [14 23]. Although the change from parabolic to linear kinetics has been described during oxidation in the temperature range 500 700 °C [14,18], a parabolic behavior was not found in our study over the entire temperature range. Furthermore, our results differ from the data reported in previous works in which kinetics obeyed parabolic laws during short term exposure in the interval 400 900 °C [14,20,25].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This agrees with the numerous discrepancies reported in the literature concerning kinetics, composition and structure of the oxide scale [14 23]. Although the change from parabolic to linear kinetics has been described during oxidation in the temperature range 500 700 °C [14,18], a parabolic behavior was not found in our study over the entire temperature range. Furthermore, our results differ from the data reported in previous works in which kinetics obeyed parabolic laws during short term exposure in the interval 400 900 °C [14,20,25].…”
Section: Discussionsupporting
confidence: 91%
“…Although the change from parabolic to linear kinetics has been described during oxidation in the temperature range 500 700 °C [14,18], a parabolic behavior was not found in our study over the entire temperature range. Furthermore, our results differ from the data reported in previous works in which kinetics obeyed parabolic laws during short term exposure in the interval 400 900 °C [14,20,25]. This means that the oxide scale was unable to provide effective protection from the early stages of oxidation, as deduced by the lateness for achieving the steady state.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…During this set of experiments, it was found that some of the formed tungsten oxide sublimes. This phenomena was previously observed in the same temperature range by Gulbransen and Andrew [23] and Baur et al [24]. During experimentation some of the volatilized tungsten oxide was deposited on the reactor walls forming a yellowish thin film.…”
Section: Tungsten Bars Oxidation At 800°csupporting
confidence: 81%
“…These cracks promote the oxygen transport inside the tungsten, helping the reaction take place inside tungsten bars leading to an increment in the thickness of the film. The cracking mechanism was previously described by Gulbransen and Andrew [23]. According to these authors, the formation of tungsten oxides is a cyclic mechanism.…”
Section: Tungsten Bars Oxidation At 600°cmentioning
confidence: 92%